Teamology: The Construction and Organization of Effective Teams - Wilde, Douglass J. (Springer, 2017)
Teamology: The Construction and Organization of Effective Teams demonstrates how psychiatrist C. G. Jung’s cognition theory, a cornerstone of modern personality typology, may be used to form and organize effective problem-solving teams through a novel quantitative transformation of numbers from the Myers-Briggs Type Indicator (MBTI) psychological instrument directly on to Jung’s eight cognitive modes. The resulting quantitative mode scores make obvious what is needed to make a good team. The product of sixteen years of studying student teams in engineering design project courses at Stanford University, Teamology: The Construction and Organization of Effective Teams is of value to educators in charge of engineering project courses, as well as to students and working professionals on project teams at all levels of engineering, architecture and business. The book is also useful for users of MBTI, and counselors interested in personal self-awareness and the development of interpersonal ability.